CD8+CD28null T Lymphocytes are Associated with the Development of Atrial Fibrillation after Elective Cardiac Surgery - Kazem, Niema; Sulzgruber, Patrick; Thaler, Barbara; Baumgartner, Johanna; Koller, Lorenz; Laufer, Günther; Steinlechner, Barbara; Hohensinner, Philipp; Wojta, Johann; Niessner, Alexander (Thrombosis and Haemostasis, 2020)
Background Postoperative atrial fibrillation (POAF) is assumed as a complex and multifactorial interaction of different pathogenic factors. Data suggests an inflammatory process as the main trigger of this specific type of atrial fibrillation. CD8+ T lymphocytes that lack the surface protein CD28 were found to be crucially involved in chronic inflammatory processes within the cardiovascular system. Of utmost interest, these so-called CD8+CD28null T cells are known to present with autoaggressive behavior and deleterious cytotoxic effects on human tissue.Methods A total of 129 patients undergoing elective cardiac valve and/or coronary artery bypass graft surgery were enrolled. Fluorescence-activated cell sorting was performed to investigate lymphocyte subsets. Patients were stratified in two subgroups according to patients developing POAF (n = 60) and individuals free of POAF (n = 69).Results Comparing patients developing POAF to individuals free of POAF, the fraction of CD8+ lymphocytes was significantly higher in individuals developing POAF (30.5% [POAF] vs. 25.7% [no-POAF]; p = 0.021). Interestingly, also the fraction of CD8+CD28null T lymphocytes was significantly higher in the POAF subgroup (66.7% [POAF] vs. 61.6% [non-POAF]; p = 0.043). Multivariate logistic regression proved that the fraction of CD8+CD28null cells is a strong and independent prognosticator for the development of POAF with an adjusted odds ratio per 1 standard deviation of 3.21 (95% confidence interval 1.01–10.18; p = 0.048).Conclusion We found that cytotoxic CD8+CD28null T lymphocytes proved to be a strong and independent predictor for the development of POAF after elective cardiac surgery. Our results potentially indicate an autoimmune impact of this preexisting, highly cytotoxic T cell subset in the pathogenesis of POAF.
Keywords: postoperative; atrial fibrillation; CD8 + CD28null; T lymphocytes; cardiac surgery